2013
DOI: 10.1080/00268976.2013.796412
|View full text |Cite
|
Sign up to set email alerts
|

VO2+–hydroxyapatite complexes as models for vanadyl coordination to phosphate in bone

Abstract: We describe a 1D and 2D ESEEM investigation of VO2+ adsorbed on hydroxyapatite (HA) at different concentrations and compare with VO2+-triphosphate (TPH) complexes studied previously in detail, in an effort to provide more insight into the structure of VO2+coordination in bone. Structures of this interaction are important because of the role of bone in the long-term storage of administered vanadium, and the likely role of bone in the steady-state release of vanadium leading to the chronic insulin-enhancing anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
4
6
0
Order By: Relevance
“…They have suggested that the vanadyl (VO 2+ ) ion is coordinated in a tridentate, structural motif by a triphosphate group providing both equatorial and axial oxygen-donor atoms [105, 106]. Figure 16 illustrates the coordination environment of VO 2+ incorporated into the hydroxyapatite matrix of mineralized bone tissue compatible with the results of ESEEM studies [105, 106]. Examples of phosphate groups axially coordinated to VO 2+ have not been previously observed.…”
Section: Biological Action Of Vo2+-chelatessupporting
confidence: 62%
See 1 more Smart Citation
“…They have suggested that the vanadyl (VO 2+ ) ion is coordinated in a tridentate, structural motif by a triphosphate group providing both equatorial and axial oxygen-donor atoms [105, 106]. Figure 16 illustrates the coordination environment of VO 2+ incorporated into the hydroxyapatite matrix of mineralized bone tissue compatible with the results of ESEEM studies [105, 106]. Examples of phosphate groups axially coordinated to VO 2+ have not been previously observed.…”
Section: Biological Action Of Vo2+-chelatessupporting
confidence: 62%
“…Of considerable interest is that Dikanov and coworkers have analyzed the superhyperfine couplings of 1 H and 31 P nuclei in the vicinity of VO 2+ sites measured by application of ESEEM spectroscopy. They have suggested that the vanadyl (VO 2+ ) ion is coordinated in a tridentate, structural motif by a triphosphate group providing both equatorial and axial oxygen-donor atoms [105, 106]. Figure 16 illustrates the coordination environment of VO 2+ incorporated into the hydroxyapatite matrix of mineralized bone tissue compatible with the results of ESEEM studies [105, 106].…”
Section: Biological Action Of Vo2+-chelatessupporting
confidence: 56%
“…Such a dispersion of isotropic hyperfine coupling constants, i.e., "a-strain," has been observed previously in both solid-state 16,39 and molecular systems. 40,41 It results from structural fluctuations of the ligand environment around the paramagnetic metal center, which, in our case, can be associated with different locations of Cr 5+ in the lattice, where it experiences slightly different coordination geometries as indicated by DFT calculations (vide infra). The isotropic hyperfine couplings can thus be explained in terms of spin density transfer to 27 Al ions in the second coordination sphere through directly coordinated oxygens and are particularly sensitive to structural variations, the values depending markedly on the M−O−Al bond angle and distance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[29] Unfortunately, references for the comparison of experimental and calculated 31 P hyperfine values for vanadyl ions are scarce. [39,40] Analyzing the experimental HYSCORE spectrum, relative amplitudes cannot be used to estimate the ratio of 31 P, 19 F, and 1 H because the system is overparameterized. First, the amplitudes for specific nuclei and specific hyperfine characteristics are nontrivial.…”
Section: Discussionmentioning
confidence: 99%